Biotechnological properties of Bacillus amylolyquefaciens B65 isolated from an artisanal tannery - Virgili Alemán, Inés María (2024)
Leather industry is traditionally characterized by the use of large amounts of chemical agents, some of which are toxic for to human health and the environment. However, during the last years, many efforts have been made with the aim of successfully implement enzymes as agents for different leather production stages. The lipopeptides produced by the Bacillus spp. genus have excellent surfactants and antibacterial properties and may collaborate in the soaking stage of leather processing as well as in the leather preservation. Moreover, Bacillus sp. proteases and lipopeptides can be co-produced in one culture medium, saving the production costs.In the present work, a screening of enzymatic activities was performed to on 11 strains of the Bacillus sp. genus that have been isolated from samples of an artisan tannery from Salta, Argentina. In particular, the ability of B. amyloliquefaciens B65 to degrade α-type (nails, hair, wool) and β-type (feathers) keratin was demonstrated by scanning electron microscopy (SEM). The co-production of proteases, keratinases, glycosidases, and lipopeptides of this strain was conducted at 37 °C in mineral media supplemented with chicken feathers. In these nutrient-poor media, the strain secreted amylases, pectinases, proteases, keratinases, and collagenases. A MALDI-TOF study also revealed that the strains secreted homologues of kurstakins, iturins, surfactins, and fengycines lipopeptides families. Therefore, B. amyloliquefaciens B65 presents great industrial potential applications, not only for tanneries but also for other industries such as pharmaceuticals, food, textiles, and detergents, among others.